Avaliação clínica e molecular do efeito do laser de baixa intensidade na prevenção da mucosite oral em pacientes submetidos a transplante de medula óssea - Silva, Geisa Badauy Lauria (2014)
Patients undergoing hematopoietic stem cell transplantation (HSCT) are submitted to a conditioning regimen of high-dose chemotherapy, which usually results in oral ulcerations. Oral mucositis (OM) is a common, painful and debilitating toxicity side effect of autologous and allogeneic HSCT. Currently, there is no intervention that is completely successful in preventing OM. Low-level laser therapy (LLLT) has been reported to produce basic effects such as anti-inflammatory activity, biomodulation and analgesia, however the biochemical responses are not well understood. The aim of this study was to evaluate the effect of LLLT on the severity of chemotherapy-induced OM and on inflammatory mediator concentration in saliva and blood in HSCT patients. Twenty-five patients were randomly assigned to 2 groups: control and laser. The laser group (n=11) received the hospital oral hygiene protocol, and low-intensity laser irradiation (660 nm, 40 mW, 4J/cm2 ) was applied from the first day of the conditioning regimen until D+7. The control group (n=14) received only the hospital oral hygiene protocol. The severity of OM (WHO scale) was scored from D0 to day 20 after transplantation (D+20). Saliva and blood were collected from all patients on admission and one day before the transplantation (D-1), on days 3 and 7 after transplantation (D+3 and D+7) and on marrow engraftment day (ME). The concentration of inflammatory mediators (TNF-α, IL-6, IL-1β, IL-10, TGF-β, EGF, FGF, VEGF, MMP2/TIMP-2, MMP9/TIMP-2) were measured using the enzyme-linked immunosorbent assay (ELISA) test. Clinical results showed less severe OM in the laser group (p < 0.05). On analysing the inflammatory mediators, the LLLT group showed increased MMP2/TIMP2 levels in saliva on D+7 (p = 0.04). In addition, significant differences were also observed for IL-10 in blood plasma on D+7 and on ME, when compared to the control group (p < 0.05). No significant differences in saliva and blood were observed for the other inflammatory mediators investigated. We concluded that LLLT was clinically effective in reducing the severity of chemotherapy-induced OM in HSCT patients, and that its mechanism of action does not seem to be completely linked to the modulation of pro- or anti-inflammatory cytokines, growth factors or matrix metalloproteinases.